Collection and Distribution of Mahua (Madhuca longifolia), Tendu (Diospyros melanoxylon) and other NTFP's in Critical Tiger Connectivity Corridor of Maharashtra - Nair, Anil Kumar; Raut, Mahendra Bhojram; Ashraf, Manisha; Thanekar, Rajat (Indian Forester, 2021)
Vidarbha Tiger Landscape in Maharashtra is an important Tiger Panthera tigris tigris connectivity linkage between Central India Tiger Conservation Landscape. The Nagzira Nawegaon Brahmapuri landscape acts as sinks for the Tiger source populations between Tadoba, Pench and Kanha Tiger Reserves from North to South and Vice Versa. These corridors are inhabited with several villages, dependent on the forest resources for subsistence and supplementary income. The major source of supplementary income post agriculture period for villages are collection of Tendu (Diospyros melanoxylon), Mahua (Madhuca longifolia) and other Non-Timber Forest Produces, also the trigger points for human wildlife conflict. Several programmes on reducing dependence on forest resources are implemented in these connectivity corridors by government agencies and Non-Government Organizations. This study from Vidarbha Landscape, first time documents collection and distribution of two of the most collected and other selective NTFP tree species in village common and agriculture areas, between the two Tiger connectivity corridors; Nagzira Nawegaon Tiger Reserve and Brahmapuri Forest Division near Tadoba Andhari Tiger Reserve in Maharashtra. The findings of study indicate marginal landholders and landless more dependent on collection of these resources. The findings of the study contribute towards developing inclusive corridor and conflict management plan for both the regions.